FRACTURE AND ORIENTATION EFFECT TO UNIAXIAL COMPRESSIVE STRENGTH AND ULTRASONIC WAVE VELOCITY IN CONCRETE SAMPLE WITH DIFFERENT COMPOSITION - Budi Nugraha, Aditya
about effect of fractures on the compressive strength and ultrasonic wave velocity (Vp). The sample used is concrete with a cement-sand mixture with composition ratio of 1:1 and 1:3. The two compositions are made to represent the strength of the weak and strong rocks. The fractures were artificial fractures made in a sample with dimension 5.5 cm x 12 cm, the artificial fractures were varied with the number and orientation of the angles. Artificial fractures varied with the some frequency of fractures made laterally/horizontally with the frequency number is 1, 2 and 3. While the fracture varied to the angle was made only one fracture with a variation of the angle is 0o, 30o, 45o, 60o, and 90o for each mixture composition and made in natural and saturated conditions. The UCS tests were carried out using the Hung Ta UCS machine to determine the effect of fracture on uniaxial compressive strength and P wave velocity (Vp). UCS testing was only carried out for samples with variations in the frequency of fractures. Meanwhile, measurement the parameter of wave velocity P (Vp) applied in samples with variations in the frequency of fractures and the orientation of the angle of the fracture. This study also aims to determine the correlation of the effect of fracture on rock strength and wave velocity, the correlation obtained is expected to be used as a guide regarding the effect of the number of fractures in the lateral position on rock strength and the effect of fracture on the value of wave velocity, which application can be used to determine the presence of fractures in concrete or rock measurements.